Hydrological characteristics and primary production in fish ponds manured with different organic manures - Singh, V K; Sharma, A P (Indian Journal of Fisheries, 2011)
The present study describes the effect of three organic manures viz. cowdung, pigdung and poultry excreta on various hydrobiological parameters and gross primary productivity in ponds stocked with Labeo rohita. Poultry excreta showed higher values of dissolved oxygen, pH, carbonate and bicarbonate alkalinity and gross primary productivity while cowdung recorded higher values of free carbondioxide than the other two manured ponds. The hydrological characteristics and gross primary productivity profiles of ponds reveal that the poultry excreta had better manurial value followed by pigdung and cowdung